Antioxidant and antimicrobial activities of Turkish endemic Achillea species - Turkoglu, Ismail; Turkoglu, Semra; Celik, Sait; Kahyaoglu, Mustafa (Academic Journals, 2010)
This study was undertaken to examine in vitro antioxidant, radical scavenging and antimicrobial activities of extracts of Achillea schischkinii Sosn. and Achillea teretifolia Waldst. and Kitt (Asteraceae). The plant materials were extracted in methanol, water and chloroform using rotary evaporator apparatus. The extracts were screened for antioxidant activity using the ABTS radical scavenging capacity, DPPH radical scavenging capacity, superoxide anion radical scavenging, hydrogen peroxide scavenging and metal chelating activities and compared to standard antioxidants. The results obtained in this study indicate that A. schischkinii and A. teretifolia are potential sources of natural antioxidants, antimicrobial activity screening was performed by the disc diffusion method against 6 bacteria strains and 2 yeast species. A. teretifolia displayed strong inhibitory effects against Pseudomonas aeruginosa. The A. teretifolia extract also showed antimicrobial activity against Saccharomyces cerevisae. I contrast, the A. schischkinii extract showed no antimicrobial activity against gram-positive and gram-negative bacteria nor against yeast.
Keywords: Achillea schischkinii; Achillea teretifolia; antioxidant; antimicrobial